Male Selenoprotein F-Like (SPF-L) Influences Female Reproduction and Population Growth in Nilaparvata lugens (Hemiptera: Delphacidae) - Ge, LinQuan; Zhou, YongKai; Gu, HaoTian; Wu, Qing; Zhou, Ze; Zheng, Sui; Stanley, David; Song, QiSheng (Frontiers in Physiology, 2019)
Selenoproteins serve in anti-oxidant and cellular redox functions in almost all organisms. A recent study characterized a selenoprotein F-like (SPF-L) in the brown plant hopper (BPH), Nilaparvata lugens, male accessory glands (MAGs), raised the question of whether the SPF-L is associated with female fecundity. In this study, SPF-L mRNA was found enriched in the internal reproductive organ (IRO) of virgin males, also expressed relatively stable in virgin males and females, and dietary dsSPF-L-treatments led to reduced MAG protein and Arginine content. Knockdown of NlSPF-L in unmated males did not influence juvenile hormone (JH) III and ecdysteriod titers, however, dsSPF-L-treated mated males had increased JH III titer, and reduced ecdysteriod titer compared to controls. After mating with dsSPF-L-treated males, female partners had reduced fat body and ovary soluble protein, JH III tier and vitellogenin (Vg) mRNA levels but no alterations in ecdysteriod titer, body weight or longevity. The experimental females had prolonged pre-oviposition periods and they laid fewer eggs, which suffered reduced hatching rates and population growth index. Such mated also led to impaired IRO development in males and females, which was confirmed by immunofluorescence staining. We infer that SPF-L acts in reproductive success of males and their partners.